Advanced Composites and Applications (15th February, 2022, Riga, Latvia) : Book of Abstracts - 80th International Scientific Conference of the University of Latvia (Institute for Mechanics of Materials, 2022)
The section ‘Advanced Composites and Applications’ was organized by the Institute for Mechanics of Materials of the University of Latvia (LU MMI) on 15.02.2022 as a part of the annual 80th scientific conference of the University of Latvia. It was organized remotely in Zoom. The official language of the section was English. The duration of the presentation was 10-15 minutes. The section was devoted to the discussion of the recent results within following topics: structure and properties of polymers and polymer-based composites, long-term properties, creep, and environmental ageing, composites for advanced applications, mechanical aspects of technology, multifunctional properties.
Keywords: Research Subject Categories::TECHNOLOGY::Engineering mechanics::Mechanical and thermal engineering; Research Subject Categories::TECHNOLOGY::Engineering mechanics::Mechanical manufacturing engineering; Research Subject Categories::TECHNOLOGY::Materials science::Functional materials